Kierunek chiński w paradyplomacji polskich regionów i miast - Modzelewski, Wojciech Tomasz (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2022)
Aktywność zagraniczna (paradyplomacja) samorządów terytorialnych jest jednym z elementów polskiej polityki zagranicznej oraz jednym z wymiarów współczesnych stosunków międzynarodowych. Artykuł prezentuje rezultaty badań współpracy polskich samorządów z Chinami, które są najczęściej wybieranym kierunkiem spośród wszystkich państw pozaeuropejskich.

The foreign activity (paradiplomacy) of local governments is one of the elements of Polish foreign policy and one of the dimensions of contemporary international relations. This paper presents the re sults of the investigations concerning foreign activity of Polish regions and cities with China. Studies have shown, that China is the most frequently chosen direction of activity of Polish local governments among all non-European countries.
Chinese direction in the paradiplomacy of Polish regions and cities
Keywords: paradyplomacja; umowy partnerskie regionów i miast; Polska; Chiny; paradiplomacy; partnership agreements of regions and cities; Poland; China